2001
DOI: 10.1023/a:1020006909285
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Locomotor disability, as defined by difficulties in activities of daily living related to lower limb function, can be the consequence of diseases and impairments of the cardiovascular, pulmonary, nervous, sensory and musculoskeletal system. We estimated the associations between specific diseases and impairments and locomotor disability, and the proportion of disability attributable to each condition, controlling for age and comorbidity. The Rotterdam Study is a prospective follow-up study among people aged 55 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Within the topics of locomotor diseases and disability we have reported that heart failure, COPD, diabetes mellitus and chronic disorders leading to locomotor complaints, are risk factors which contribute considerably to locomotor disability [114, 115]. In relation to osteoporosis we have determined the incidence of vertebral [116] and non-vertebral fractures [117], and the relationship between bone mineral density (BMD), BMD change and the occurrence of fracture [117], as well as with heel ultrasound measurements [118] and bone resorption markers [119].…”
Section: Endocrine Diseasesmentioning
confidence: 99%
“…Within the topics of locomotor diseases and disability we have reported that heart failure, COPD, diabetes mellitus and chronic disorders leading to locomotor complaints, are risk factors which contribute considerably to locomotor disability [114, 115]. In relation to osteoporosis we have determined the incidence of vertebral [116] and non-vertebral fractures [117], and the relationship between bone mineral density (BMD), BMD change and the occurrence of fracture [117], as well as with heel ultrasound measurements [118] and bone resorption markers [119].…”
Section: Endocrine Diseasesmentioning
confidence: 99%
“…In particular, myocardial infarction is a major cause of chronic disability and mortality in the elderly [1]. Aged hearts exhibit low tolerance to various forms of stress, including oxidative stress induced by ischemia/reperfusion (IR).…”
Section: Introductionmentioning
confidence: 99%
“…Poor lower-body function plays a crucial role in the disablement process and has been associated with increased disability days, physician contacts, fear of falling, falls, hip fracture, depression, nursing home placement, and mortality [2,3]. Not surprisingly, diabetes is a major risk factor for the development of lower-body-related functional limitations [4], and a substantial portion of population (adult) disability related to lower-extremity functioning is attributable to diabetes [5]. In the United States lower-body functional limitations are especially high among urban African Americans [6].…”
Section: Introductionmentioning
confidence: 99%